Bismuth(III) and diorganotin(IV) complexes of bis(2-acetylpyridine) thiocarbonohydrazone: Synthesis, characterization, and apoptosis mechanism of action in vitro. (15th November 2018) - Fang, Yan; Wang, Yu-Ting; Zhao, Meng; Lu, Yan-Li; Li, Ming-Xue; Zhang, Ya-Hong
Graphical abstract: Molecular mechanism of1 inducing apoptosis against human hepatocellular carcinoma HepG2 cells has been discussed in detail. Biological research illustrated that1 exhibited higher activity against HepG2 cells. Cytotoxicity experiments involving with mitochondria indicated that1 restrained cells growth in a dose-dependent manner. Protein analysis revealed that1 restrained Bcl-2 expression and accelerated Bax expression, inducing caspase-3 activation. Abstract: In this paper, three bismuth(III) and diorganotin(IV) complexes based on bis(2-acetylpyridine) thiocarbonohydrazone (H2 L) have been fully designed. The tests of the complexes on inhibiting human hepatocellular carcinoma HepG2 cells growth in vitro revealed that the complexes have higher activity against HepG2 cells but much less toxicity toward normal hepatocyte QSG7701 cells. Particularly, 1 exhibited higher activity with a lower IC50 value (compound concentration that produces 50% of cell death, 3.42 ± 0.25 µM). Moreover, cytotoxicity experiments involving with mitochondria confirmed that1 restrained cells growth in a dose-dependent manner. Protein analysis indicated that1 restrained Bcl-2 expression and accelerated Bax expression, inducing caspase-3 activation.